2010
DOI: 10.1016/j.otohns.2010.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis in thyroid surgery: Harmonic scalpel versus other techniques—a meta‐analysis

Abstract: There is clear evidence that using the harmonic scalpel for hemostasis in thyroid surgery significantly reduces operating time and blood loss and that it is not associated with an increase in volume of drainage fluid, complication rate, or hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
112
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 29 publications
13
112
1
6
Order By: Relevance
“…10 The systematic review by Ecker et al shows difference in the mean VAS of 0.86. 13 In a study by Miccoli et al the VAS noted on 24 hours was less in ultrasonic group (3.9) as compared to 5.3 in the conventional group, similar findings were noted at 36 hours (2.27 vs 3.95).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…10 The systematic review by Ecker et al shows difference in the mean VAS of 0.86. 13 In a study by Miccoli et al the VAS noted on 24 hours was less in ultrasonic group (3.9) as compared to 5.3 in the conventional group, similar findings were noted at 36 hours (2.27 vs 3.95).…”
Section: Discussionmentioning
confidence: 64%
“…12 Ecker et al found the overall drain to be 20.03 ml less while operating with ultrasonic device. 13 Aziz et al found the postoperative drain on 1 st POD to be only 18.2 ml in comparison to 76 ml in conventional techniques. 10 The systematic review by Ecker et al shows difference in the mean VAS of 0.86.…”
Section: Discussionmentioning
confidence: 94%
“…The single‐use device, HARMONIC FOCUS ® (Ethicon Endo‐Surgery, Johnson & Johnson, Cincinnati, Ohio, USA), has been evaluated in a number of clinical studies with discordant results. Although it is generally acknowledged that use of US reduces operating time7, 8, 9, 10, the impact on postoperative complications is unclear. Some studies have reported lower rates of complications, whereas others failed to demonstrate benefits over conventional haemostasis (CH)8, 9, 10, 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, a potential drawback is, for some authors, the increased health care costs (10)(11)(12)(13)(14)(15)(16). In addition, EBD are essential for endoscopic procedures (16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%